Pulmonary Silicosis Presents with Pleural Effusion - Mohsin Salih; Tarake Aljarod; Mohamed Ayan; Melnick Jeffrey; Bobby H. Shah (Case Reports in Medicine)
Silica and silicate mineral dust inhalation can cause a variety of histopathological changes in the lungs and pleura. These include pulmonary silicotic nodules, interstitial infiltrate, fibrosis, and pleural thickening. Pleural effusion is an extremely rare presentation of silicosis. To our best knowledge, there have been only 2 cases of silicosis with pleural effusion reported in medical literature. Herein, we describe a case of a 77-year-old male with almost 50 years’ history of occupational silica exposure. He presented with a 4-week history of exertional shortness of breath. He is a lifetime nonsmoker, with no known other significant pulmonary disease. He had chest X-ray which showed a right lung infiltrate and bilateral pleural thickening and effusion. Chest CT showed moderate-sized bilateral pleural effusion and thickening with multiple bilateral intrapulmonary nodules seen. He had undergone extensive workup and was diagnosed with silicosis.